(3GdYHQ hGdGYJHGQs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfg djS HCgd GdHQ hGdJbhi Zfi Yf GdJhGYX s
(3BNQgG (B:s
(3hgh bdjd ef cKjQ, hLRA ef cd, aCeG GdYde GdcGed aYfO GdNdGb Je GdcJGH s
(3YdjgG ebGHdI JeJ ai SfI GdfSN(B1349 (3hGNQi SfI (B1365(3g`s
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi eY GNJdGa aj HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B7s
Keywords: (3GdCOHs